The sustainability of yachting tourism: A case study on Greece - Jamie Chen; Chrysanthi Balomenou; Peter Nijkamp; Panoraia Poulaki; Dimitris Lagos (European Regional Science Association (ERSA), 2016)
Yachting tourism is an emerging industry in coastal regions, particularly in the Mediterranean countries. The rising success of yachting tourism induces a significant boom in its relevant business segments. As a type of leisure tourism, yachting tourism plays a big role in an experience economy, and its positive impact on coastal regions has meant a substantial contribution to the local economy. Greece has many (potential) advantages to acquire a dominant position in developing a yachting tourism industry, such as authentic local attractions, natural coastal resources, etc. However, since the appearance of the current global financial crisis in 2007, the yachting tourism industry in this country has manifested a clear downturn, while the implementation of some austerity measures have aggravated the economic prospects. Meanwhile, the intense industry competition from some neighboring countries prompt a big challenge on the sustainability of the Greek yachting tourism industry. The main objective of our research is to map out the backgrounds and environments of the unfortunate situation. On the one hand, we compare Greek yachting tourism sector with similar sectors in other competitive Mediterranean countries, in order to identify the problems in strategic policy-making. On the other hand, we conduct extensive field research on yacht users and other stakeholders, in order to model and understand the factors relevant to its sustainable development. For achieving the aforementioned aims, both theoretical research in sustainability and the empirical aspects of the Greek yachting tourism industry will be allowed. The modelling results demonstrate that relevant industry policies have influenced the sustainability of the Greek yachting tourism negatively; our comparative study prospects also new knowledge to guide the sustainable development of the Greek yachting tourism from the perspective of other countries' strategies. Furthermore, the field surveys of yacht users and other stakeholders allow us to identify the relevant factors of sustainability in the Greek yachting tourism industry. In addition, our study sheds also new light on the emerging research field of the yachting tourism economy, and it leads to an enrichment of traditional tourism research. As our empirical research focusses in particular on the Greek yachting tourism industry, our findings provide practical guidance for the development of the Greek yachting industry in a long run.
Keywords: C8; L83; L98; O18; R58; Y60; Z3; Z32; Z38; 330; yachting; tourism; sustainability; Greece